2004
DOI: 10.1111/j.1600-0463.2004.apm1120608.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of hydrolytic enzymes in fungi isolated from diabetic pregnant women: Is there any relationship between fungal alkaline and acid phosphatase activity and glycemic control?

Abstract: Ability to respond to environmental changes and secretion of hydrolases are considered to be important for Candida virulence. In this study we determined and compared the activities of 19 different hydrolases of the fungal strains isolated from diabetic and non-diabetic pregnant women. We also looked for the presence of a relationship between hydrolase activities and glycemic control, and, furthermore, evaluated the influence of gestational age on the activity of hydrolases. Mycological examinations were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…[ 39 ] During pregnancy, elevated hormone levels and glycogen accumulation in the vagina lead to a rise in VVC frequency, about 2 folds compared with nonpregnant women. [ 23 , 24 , 29 31 , 40 ] It is generally believed that pregnant women with GDM are predisposed to Candida colonization of the vagina. [ 25 – 28 ] Elevated glycemia in the vaginal tissue increases fungus adhesion and growth, predisposing the vaginal epithelial cells to binding to Candida albicans cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 39 ] During pregnancy, elevated hormone levels and glycogen accumulation in the vagina lead to a rise in VVC frequency, about 2 folds compared with nonpregnant women. [ 23 , 24 , 29 31 , 40 ] It is generally believed that pregnant women with GDM are predisposed to Candida colonization of the vagina. [ 25 – 28 ] Elevated glycemia in the vaginal tissue increases fungus adhesion and growth, predisposing the vaginal epithelial cells to binding to Candida albicans cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 – 28 ] Elevated glycemia in the vaginal tissue increases fungus adhesion and growth, predisposing the vaginal epithelial cells to binding to Candida albicans cells. [ 23 , 24 ] In addition, glycemia of 10 to 11 mmol/L could impair host defense mechanism, and hyperglycemia decreases neutrophil nonpurposeful migration and weakens their chemotactic and phagocytic powers, thereby elevating diabetic patient's sensitivity to VVC. [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning bacterial vaginosis even less evidence is available for women with GDM. On the one hand, it appears logically consistent that diabetic pregnant women more likely acquire genital infections, because of poor metabolic control, higher body mass index (BMI) and potentially impaired leucocyte function [ 15 , 16 ]. Moreover, pregnancy itself harbours an immunocompromised state, leading to an increased risk of vaginal Candida colonization [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…reported that PSA levels prior to inoculation were very low, increased dramatically after inoculation and showed a strong dose response such that increasing amounts of semen yielded increased amounts of PSA. Another shortcoming of the use of AP was described by Nowakowska and colleagues 25 . In this report, vaginal fungi were shown to release AP; thus, the presence of a fungal vaginal infection could produce erroneous assessment of the presence of semen.…”
Section: Discussionmentioning
confidence: 75%